Business and the post-revolutionary State: Elite re-ordering and the new strategy of collaboration in Nicaragua - Spalding, Rose J. (2017)
This study examines the political processes that affected economic elite re-configuration in Nicaragua during the 1980s and 1990s, and it documents the shifting patterns of business-state relations following the return to power of Sandinista leader Daniel Ortega in 2007. Drawing on documents and interviews with representatives of business, government and NGO, this article traces the rise and fall of traditional elite factions during the Sandinista Revolution and analyzes the impact of market reform on changing elite dynamics during the post-revolutionary transitions that followed. This background helps to explain the business sector’s new strategy of sustained negotiation and collaboration with the government following Ortega’s re-election and rising political dominance. The article concludes by raising questions about the stress points and unresolved problems that remain.